Non-alcoholic fatty liver disease causally affects the brain cortical structure: a Mendelian randomization study - Lin, Yu-Kai; Cai, Xin-Ran; Chen, Jiang-Zhi; Hong, Hai-Jie; Tu, Kai; Chen, Yan-Ling; Du, Qiang (Frontiers in Neuroscience, 2024)
Background Reduced brain volume, impaired cognition, and possibly a range of psychoneurological disorders have been reported in patients with non-alcoholic fatty liver disease (NAFLD); however, no underlying cause has been specified. Here, Mendelian randomization (MR) was employed to determine the causative NAFLD effects on cortical structure. Methods We used pooled-level data from FinnGen’s published genome-wide association study (GWAS) of NAFLD (1908 cases and 340,591 healthy controls), as well as published GWAS with NAFLD activity score (NAS) and fibrosis stage-associated SNPs as genetic tools, in addition to the Enigma Consortium data from 51,665 patients, were used to assess genetic susceptibility in relation to changes with cortical thickness (TH) and surface area (SA). A main estimate was made by means of inverse variance weighted (IVW), while heterogeneity and pleiotropy were detected using MR-Egger, weighted median, and MR Pleiotropy RESidual Sum and Outlier to perform a two-sample MR analysis. Results At the global level, NAFLD reduced SA (beta = −586.72 mm2, se = 217.73, p = 0.007) and several changes in the cortical structure of the cerebral gyrus were found, with no detectable pleiotropy. Conclusion NAFLD causally affects cortical structures, which supports the presence of an intricate liver–brain axis.